'Non-Amending' Provisions in a Constitutional Amendment: A Practical Application to the 'Transition Period' under the 101st Constitution Amendment Act, 2016. (16th December 2019) - Prasanna Bhattacharya, Aditya; Makkar, Kashish
Abstract: Amendments to the constitution and the jurisprudence surrounding the constituent power of Parliament have traditionally dominated the field of Indian constitutional law and constitutionalism. Most debates in this field have been restricted to issues like the source of the amending power of Parliament, express, and implied limits on the power to amend, and so on. In an attempt to revert to the core principles of constituent power, this paper attempts to answer more basic but extremely compelling constitutional questions: to qualify as an amendment to the constitution, how exactly must an amendment affect the text of the constitution? If an amendment does not change the bare text of the constitution in any way, but merely affects the overall constitutional scheme, can it still be accorded the status of a constitutional amendment? Locating this issue in the extension of the compensation period under the GST regime in India, this paper seeks to provide an answer to these questions by using a practical setting. First, the source of parliamentary competence to bring about such an amendment is traced. By the use of constitutional theory and principles of statutory interpretation, is then demonstrated that such 'non-amending' provisions are undoubtedly an inherent part of the constitutional regime. Lastly, this paper proposes a model that covers both legislative powers of Parliament, that is, constituent power and ordinary law-making power. In the nature of a walk-through, this model explains the legislative process to be followed to bring about an extension of the compensation period.